Geo-epidemiology of animal tuberculosis and Mycobacterium bovis genotypes in livestock in a small, high-incidence area in Sicily, Italy - Marianelli, Cinzia; Verrubbi, Vladimiro; Pruiti Ciarello, Flavia; Ippolito, Dorotea; Pacciarini, Maria Lodovica; Di Marco Lo Presti, Vincenzo (Frontiers in Microbiology, 2023)
The persistence of animal tuberculosis (TB) in livestock is a major concern in Sicily, Italy. The objective of this study was to elucidate the transmission dynamics of M. bovis infection in a highly circumscribed, and at the same time geographically diverse, high-risk area of the island through an in-depth geo-epidemiological investigation of TB in cattle and black pigs raised in small-scale extensive farms across the district of Caronia. We used genotype analysis coupled with geographic information system (GIS) technology and phylogenetic inference to characterize the spatial distribution of TB and M. bovis genotypes in livestock and the genetic relationships between M. bovis isolates. A total of 589 M. bovis isolates collected from slaughtered cattle (n= 527) and Sicilian black pigs (n=62) over a five-year period (2014-2018) were included in the study. TB was widespread throughout the district and was most frequent in the north-central area of the district, especially along one of the district's streams. We identified a total of 62 M. bovis genotypes. Identical genetic profiles were isolated from both neighbouring and non-neighbouring herds. The ten most frequent genotypes, accounting for 82% of M. bovis isolates, showed geographic specificities in that they tended to cluster in specific spatial niches. The landscape structure of these niches – i.e. steep slopes, rocky ridges, meadows and streams – is likely to have had a significant influence on the distribution of TB among livestock in Caronia. Higher concentrations of TB were observed along streams and in open meadows, while rocky ridges and slopes appeared to have hampered the spread of TB. The geographical distribution of TB cases among livestock in Caronia is consistent with several epidemiological scenarios. Landscape structure is likely to play an important role in the transmission and persistence of M. bovis infection across the district. Additional potential risk factors, such as livestock trading and extensive breeding methods, are also discussed. Our results will contribute to the improvement of surveillance, control and eradication activities of TB in Sicily by the implementation of ad hoc TB control measures, especially in farms located along streams, sharing common pastures or with mixed animal species.